Загублена «намистина» «Зів’ялого листя» - Салій, О. (Слово і Час, 2021)
У статті докладно розглянуто не опублікований за життя І. Франка
вірш «Душе моя! Душе душі моєї!». З’ясовано його жанр, творчу історію, особливу увагу звернено на психобіографічний контекст. В основі
поетичної рефлексії — інтимні почуття поета до польки Целіни Журовської, тому в статті приділено увагу цій жінці, зокрема її впливу
на творчість І. Франка. Вірш проаналізовано з погляду його архітектоніки, поетичної композиції та іконосфери. Виокремлено художні
образи перлини (мушлі) та душі. Звернено увагу на поетичну мову й
версифікацію. У дослідницькому фокусі також перебувають інші твори
письменника (поетичні, прозові), що певною мірою стосуються Ц. Журовської, зокрема й вірші зі збірки «Зів’яле листя». The paper deals with the poem by Ivan Franko “My soul! The soul of my soul!”, which wasn’t
published during the poet’s lifetime. As one of the poems from Franko’s poetic cycle “The
First Bunch” it might have been included in the forthcoming collection “The Withered
Leaves”. That’s why the general context of this collection is relevant. The researcher reviews
context. The comparison of the published text with the autograph revealed a discrepancy
that modifies interpretation.
The basis of this poetic reflection is the poet’s intimate feelings for Celina Żurowska
(married name Zygmuntowska), so the paper focuses on this Polish woman, in particular
her attitude to the poet and her influence on his work. The research focus also includes
other works of the writer, which somehow relate to Celina. Her pride, stubbornness, and
sometimes even contempt caused pain in the poet’s soul, which gave rise to poetic masterpieces.
The memories of Franko’s contemporaries, as well as the ones of Celina herself, help
to interpret the poem.
The researcher analyzed the work in terms of its structure, poetic composition, emotional
tone, and iconosphere. The images of the pearl (shell) and the soul, which are the central
symbols of this work, show semantic similarity. The pearl is a symbol of love that grows
and becomes stronger due to patience, and at the same time, it is a metaphor for the soul.
The poetic language and versification have been examined as well.